Photonic Jet Suitable for High Precision Contact Laser Surgery Applications in Water - Azizi, M. K.; Alotaibi, A. A. (Engineering, Technology & Applied Science Research, 2020)
The use of contact probes in surgical laser technologies (SLT) allows tissue contact without damage and enables tactile feedback during operations. Among the materials suitable for the manufacturing of chirurgical contact probes, sapphire has been widely used. Indeed, the optical properties of this material allow the formation of a high energy density localized region at the front of the contact probe, when used in air. However, in water, this focusing effect is very weak. In this work, the use of a cylindrical sapphire contact probe associated with a continuous (CW) Nd: Yag laser (at 1064nm) is proposed and studied, which provides, in water, a narrow and high-intensity beam (photonic jet). With the evolution of technology, this kind of surgery can be done remotely. Based on 5G technology, medical experts can bring their skills to remote other practitioners around the world. The obtained results show a linear dependence of the focal length and a linear dependence of the beam intensity of the photonic jet to the cylinder radius while the full width at half maximum of the photonic jet beam shows exponential decay dependence. Such a system could give rise to a new kind of optical scalpel to the ultra-precise laser surgery in water.